2002
DOI: 10.1007/s00384-001-0378-z
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoscintigraphy in patients with primary rectal cancer: the role of total mesorectal excision for primary rectal cancer – a lymphoscintigraphic study

Abstract: Lymph vessels can be divided anatomically into visceral and somatic, and detection of extramesorectal lymph nodes does not call for lateral lymphadenectomy. Primary rectal cancer confined to the organ metastasizes within the mesorectum and does not invade extraregional lymph nodes. The mesorectum is the major visceral route for caudocranial metastatic spread.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 26 publications
0
10
0
1
Order By: Relevance
“…The identification of malignant extra-mesorectal lymph nodes by radiological detection during operation serves as evidence that there is locally generalized tumour disease. The detected lymph nodes can be excised using less invasive surgery at sites of higher radioactivity detected by a gamma probe, with a recurrence risk similar to that of the more invasive technique [7,15]. This method of detection of lymph nodes, based on the identification of the specific lymphatic drainage of the tumour and its removal, reduces the need for radical lymphadenectomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The identification of malignant extra-mesorectal lymph nodes by radiological detection during operation serves as evidence that there is locally generalized tumour disease. The detected lymph nodes can be excised using less invasive surgery at sites of higher radioactivity detected by a gamma probe, with a recurrence risk similar to that of the more invasive technique [7,15]. This method of detection of lymph nodes, based on the identification of the specific lymphatic drainage of the tumour and its removal, reduces the need for radical lymphadenectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies employing lymphoscintigraphic techniques have shown that the lymphatic drainage of the rectum occurs through the lymph ducts along the inferior mesenteric artery and of the distal third of the rectum through the lymph ducts along the internal iliac artery [6,7]. Retrograde drainage of rectal carcinoma to inguinal nodes is detectable when there is a blockage of the proximal lymph ducts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…62 63 Sterk et al reported on the detection of extramesorectal (iliac) LNs by rectal lymphoscintigraphy in four of 16 patients investigated, although they expressed doubts about the adequacy of their submucosal injections, and stated that deeper injections of the radiocolloid could be the cause for this high frequency. 91 Larger series published to date suggested that unexpected lymphatic drainage occurs in 4-8% of cases, 86 92 either as deep mesenteric SNs or as SNs "placed to the left" in cases of right sided colon tumours. The pinpointing of these LNs may lead to altered surgery if they are outside the margins of the standard resection.…”
Section: The Role Of Lymphatic Mapping In Colorectal Carcinomamentioning
confidence: 99%
“…Folglich berichten mehrere Arbeitsgruppen über eine unabhängige prognostische Bedeutung freier intraperitonealer Tumorzellen bei Karzinomen des oberen Gastrointestinaltrakts, sodass die Peritoneallavage in einigen Zentren die Staging-Laparoskopie in ihrer prognostischen Wertigkeit bereichert hat [17,18,40,96].Weitere Innovationen und Forschungsschwerpunkte auf dem Gebiet der Staging-Laparoskopie liegen im Nachweis von peritonealen Mikrometastasen mittels Fluoreszenzmethoden nach entsprechender "Markierung" mit 5-Amino-Lävulinsäure, wobei im Rahmen experimenteller Untersuchungen über positive Erfahrungen hinsichtlich Sensitivität und Spezifität berichtet wird [36]. Darüber hinaus wurden lymphoszinitigraphische Methoden und das "Sentinel-Lymphknoten-Konzept" ebenfalls in die Staging-Laparoskopie integriert [25,84,88,111].…”
Section: Stellenwert Der Staging-laparoskopieunclassified